Manicured versus naturalistic landscape style: public preference of urban park's landscape in Kuala Lumpur, Malaysia - Mohd Ariffin, Nur Diyana; Ibrahim, Roziya; Maulan, Suhardi; Abu Bakar, Shamsul (Human Resource Management Academic Research Society, 2024)
Urbanisation significantly impacts cities, altering their natural environment and greeneries into a more manicured landscape. Kuala Lumpur, Malaysia, has been experiencing a similar process of urban landscape changes since the colonial era in the early 20th Century. The government's vision of achieving a "Beautiful Garden City" has been culturally accepted and embraced by the public. Sustaining the manicured landscape demands significant maintenance effort and costs that surpass the financial capacity of the local authority. Despite the potential to manage Kuala Lumpur’s urban parks towards an environmentally sustainable approach (ESA), delivering such practice in a tropical setting creates a distinct visual appearance contrary to the current manicured landscape that would challenge the local authority to gain public acceptance. This paper draws from survey findings of 258 park users of the selected urban parks in Kuala Lumpur on their preferred landscape style from randomly arranged photos of manicured (the existing landscape scene) and the naturalistic landscape (superimposed scene). The results indicate that the public, overall approves of both landscape styles for their appearance and safety attributes. Interestingly, the public would also accept changes towards a more naturalistic style considering its environmental function and aesthetic value. particularly at the water edge, followed by shrublands and semi-woodland areas. The lawn area is the least preferred area for such a landscape, being a prime social space in the park. In conclusion, this paper offers suggestions to improve the naturalistic landscape style, encouraging the local authorities to consider adopting this approach in managing tropical urban parks.